Comparison of butt joint effects in Profiled Steel Sheet Dry Board (PSSDB) wall panel with door opening / Samsul Izwan Anwar - Anwar, Samsul Izwan (2004)
The report presents a behavior of a Profiled Steel Sheet Dry Board (PSSDB) with door opening system, which acts as a load-bearing wall. Three samples of panel were tested in this study. The overall dimension of each sample is 1320mm width and 1000mm height. The door opening dimension is 700mm x 300mm. The overall thickness of each sample is 78mm. This study used Bondek II as a profiled steel sheet and Cemboard as a dry board. A procedure has been developed for determining the deflection mode, the stressstrain relationship, the cracking pattern and the ultimate load capacity. The average ultimate load capacity for this study was 239.23kN and average maximum lateral displacement was 6.45 mm. The results have been compared with previous students' (Mohd Rashid (2003), Muhammad Zihan (2003) and Muhammad Shahriz (2004)) results.